MANAGEMENT OF VILLAGE FUNDS IN ACCORDANCE WITH PERMENDAGRI NUMBER 20 OF 2018 - Saputro, Adi; Sholihin, Muhammad Rijalus; Purnomo, Hari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The purpose of this study was to determine the suitability of the Village Fund (DD) financial management cycle in Kunir Lor Village, Kunir District, whether it was in accordance with the cycle. village financial management as regulated in the Minister of Home Affairs Regulation (Permendagri) number 20 of 2018 and to describe the Village Fund Management (DD) accountability system in Kunir Lor Village, Kunir District, Lumajang Regency. This type of research is descriptive research with a qualitative approach where the data obtained from the Office of the Village Hall of Kunir Lor, Kunir District, Lumajang Regency in the form of interviews, documentation, and questionnaires. The data used is primary data, where the data is processed from published data. The results of this study state that the management of village funds is divided into several stages including the planning stage, implementation stage, administration stage, reporting stage and accountability stage to Kunir Lor Village. process whose implementation is still considered ineffective.